Ecological, physiological and life-history traits correlate with genome sizes in decapod crustaceans - Iannucci, Alessio; Saha, Anik; Cannicci, Stefano; Bellucci, Arianna; Cheng, Christine L. Y.; Ng, Ka Hei; Fratini, Sara (Frontiers in Ecology and Evolution, 2022)
Crustaceans are characterized by some of the most variable genome sizes among animals. Significant relationships between genome size and specific eco-physiological and morphological features have been described in many crustacean taxa, such as Amphipoda, Ostracoda, Cladocera and Copepoda. A consistent pattern of genome size variation is yet to be found, however, in one of the most specious order of crustaceans, the Decapoda. We investigated how genome size is related to selected eco-physiological and life-history traits in species belonging to this order. We analyzed the respiratory, excretory and developmental adaptations of 179 decapod species inhabiting shallow marine, deep marine, freshwater, intertidal and terrestrial habitats. Our results show that the genome size is significantly larger in decapods that have a direct development. Moreover, in Anomura, Astacidea and Brachyura we found larger genome sizes in species i) living in freshwater habitats, ii) using gills as a strictly water-breathing organs, iii) presenting a direct development. While specie that i) live in shallow waters, and intertidal and terrestrial habitats, ii) have some degrees of air-breathing adaptations, namely gills that can exchange oxygen with air if wet or branchiostegal lungs and iii) possess an indirect or extended development are characterized by significantly smaller genomes. Our analyses show that developmental complexity affect genome size in decapods, and that multiple eco-physiological and life-history traits correlate with genome size in Anomura, Astacidea and Brachyura.